Resilience assessment of offshore structures subjected to ice load considering complex dependencies. (June 2022) - Ramadhani, Adhitya; Khan, Faisal; Colbourne, Bruce; Ahmed, Salim; Taleb-Berrouane, Mohammed
Highlights: Study investigates offshore structure response to an ice load using the concept of resilience. Resilience is quantified by considering absorptive, adaptive, and restorative capacities. Dependence between wind velocity and wave height is considered ice load modelling. Offshore structure in arctic should be designed considering both absorptive and adaptive capacities. Abstract: Offshore structures in arctic and subarctic regions are subjected to various natural hazards. These structures need to be designed to withstand these natural hazards and to recover quickly after an undesirable event occurs. Ice load is a significant natural hazard for structures in these regions. The magnitude of ice load depends on the ice drifting velocity, which is influenced by other environmental conditions such as wind speed and wave activity. Most studies in the literature assume independence among these influencing environmental parameters, although they have significant dependence. In addition, there are a limited number of studies focused on analyzing the capacities of offshore structures to resist ice loads. This paper investigates an offshore structure's response to an ice load, using the concept of resilience. Resilience is quantified by considering absorptive, adaptive, and restorative capacities. Dependence between wind velocity and wave height is considered in the analysis; the Gumbel-Frank Type-1 Copula function is used to model relationships between these influencing variables. The study highlights that a mono-pile vertical structure shows resilience in terms of absorptive capacity. An offshore structure in arctic conditions needs to be designed considering both absorptive and adaptive capacities.